2012
DOI: 10.1293/tox.25.63
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of Incidental Findings in Cynomolgus Monkeys (<i>Macaca Fascicularis</i>) Used in Toxicity Studies

Abstract: The purpose of our publication is to widely communicate pictures of spontaneous findings occurring in cynomolgus monkeys. Focal lymphoplasmacytic infiltration is commonly seen in the general organs. The frequency and severity of these lesions may be influenced by the administration of drugs with an effect on the immune system. Lymphoplasmacytic infiltration in the lamina propria of the stomach is also frequently seen in cynomolgus monkeys, and it is caused mainly by a Helicobacter pylori infection. Various deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
110
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 19 publications
9
110
0
Order By: Relevance
“…Previous publications on the monkey thymus focusing on normal morphology (Pearse 2006), incidental and background observations (Sato et al 2012;Kaspareit et al 2006;Spoor, Radi, and Dunstan 2008;Chamanza et al 2010), immunotoxicity (Kuper et al 2000), and age-related changes in lymphocyte subsets (W. W. Lee et al 2003;Nam et al 1998) have been valuable for the interpretation of thymus observations. We not only confirmed the light microscopic results previously reported for the normal monkey thymus but also correlated these observations to sexual and skeletal maturity parameters to characterize inherent variability in thymus parameters of cynomolgus monkeys related to maturation.…”
Section: Thymus Light Microscopic Observations Were Consistent With Wmentioning
confidence: 99%
“…Previous publications on the monkey thymus focusing on normal morphology (Pearse 2006), incidental and background observations (Sato et al 2012;Kaspareit et al 2006;Spoor, Radi, and Dunstan 2008;Chamanza et al 2010), immunotoxicity (Kuper et al 2000), and age-related changes in lymphocyte subsets (W. W. Lee et al 2003;Nam et al 1998) have been valuable for the interpretation of thymus observations. We not only confirmed the light microscopic results previously reported for the normal monkey thymus but also correlated these observations to sexual and skeletal maturity parameters to characterize inherent variability in thymus parameters of cynomolgus monkeys related to maturation.…”
Section: Thymus Light Microscopic Observations Were Consistent With Wmentioning
confidence: 99%
“…They can be pathologic findings in organs that ought to be normal as the organisms have not shown any signs of diseases. We categorize such findings as a "background or accidental" pathology [1]. Other unexpected findings include normal (or altered) structures in an unexpected location.…”
Section: Correspondencementioning
confidence: 99%
“…A lengthy dissertation covering all of the potential background lesions in NHPs is beyond the intent of this chapter; however, we refer the reader to several particularly excellent references on this topic: Sato et al [15], Chamanza [16], Chamanza et al [17], Kaspareit et al [18], and David et al [19]. As previously mentioned, these spontaneous changes can also be referred to as "incidental" or "background" changes.…”
Section: Common Background Microscopic Changes In Nhpsmentioning
confidence: 99%
“…It has been demonstrated that serum cardiac troponin I (cTnI) concentrations are not increased in cynomolgus monkeys with myocardial mononuclear cell infiltrates, and thus serum cTnI does not seem to be a biomarker that can be used to screen cynomolgus macaques for this spontaneous cardiac finding [20]. Clinical chemistry changes (e.g., increased alanine aminotransferase [ALT] or aspartate aminotransferase [AST]) are typically not associated with hepatic mononuclear cell infiltrates [15,17]. There are variations in the degree of mononuclear cell infiltrates between cynomolgus monkeys from different sources.…”
Section: Mononuclear Cell Infiltratesmentioning
confidence: 99%